Monitoring the storage conditions of wines – efficient method for consumer protection - Stancu, Adrian; Bucur Crina, Raluca (Economics of Agriculture, 2010)
To maintain constant the wine quality during its entire circulation until it meets the consumer, it is necessary that the wine must be preserved in certain conditions of temperature, atmospheric relative humidity and for limited period of time in all the stages of technical-economic circulation. The monitoring of time evolution of wines quality level according to the level of main preservation parameters can identify some correlations in order to avoid selling products with harmful influence on consumer. To emphasize the time evolution of wines quality characteristic levels preserved in standard storage conditions, the authors made a study which had as its main purpose monitoring the evolution of ten quality characteristics of Sauvignon Blanc wine during 60 days period. The research underlined changes with negative influence on quality in all four sensory characteristics and one physicochemical characteristic. These findings made on samples preserved in standard conditions but in the maximum levels of preservation parameters, conclude that the wines quality level is not always constant during the period of validity, although the standard conditions are obeyed. In this context, to ensure the wine consumer protection requires that the producers and competition companies must not only to obey the storage conditions but also to provide actions to improve the adjustment of parameters to wine preservation requirements, so that the initial wines quality level to be maintained or to have slight decreases.